Coupling Between Lithosphere Removal and Mantle Flow in the Central Andes. Issue 16 (23rd August 2021) - Wang, Huilin; Currie, Claire A.; DeCelles, Peter G.
Abstract: The central Andes is part of a Cordilleran orogen formed through continent‐ocean convergence. In contrast to the thickened crust, the mantle lithosphere below much of the orogen is anomalously thin. Additionally, the surface is characterized by widespread backarc magmatism and transient ∼100‐km‐wide basins that developed the over last 30 million years, with basins located systematically seaward of major backarc ignimbrite centers and basin formation predating the late Miocene magma/ignimbrite flare‐up. Using numerical models, we propose a novel mechanism whereby lithosphere removal is coupled with mantle flow. First, a small area of high‐density eclogitized lower crust initiates a gravitational instability, causing a localized basin at the surface that subsides and then uplifts. Foundering crust and adjacent lithosphere are entrained by subduction‐induced mantle flow, driving regional lithosphere removal and magmatism. The models demonstrate that mantle flow can amplify a local lithosphere instability to orogen‐wide lithosphere removal, rapidly eliminating accumulated mass in the orogen. Plain Language Summary: Mountain ranges develop through lithospheric shortening and thickening. However, geophysical studies show that the lower portion of many mountain ranges is "missing." Gravitational lithosphere removal has been proposed as a means to eliminate the thickened mountain root, thus enabling continued plate shortening and mountain growth. Although lithosphere removal is considered to be a crucial process in mountain belt evolution, no consensus exists regarding the removal mechanism. Here, we examine the geological and geophysical observations in the central Andes and propose a new style of lithosphere removal. Our models show that a small high‐density root beneath the mountain can trigger regional‐scale lithosphere removal, through the interaction of mantle flow. Key Points: Systematic spatial‐temporal correlations exist among transient basins, backarc ignimbrites and thinned lithosphere in the central Andes These observations can be explained by interactions between localized lithospheric instabilities and regional mantle flow A localized dense instability in lower crust is entrained by subduction‐induced mantle flow, triggering orogen‐wide lithosphere removal